COMPARATIVE ANALYSIS OF PRINCIPALS APPLICATION OF BUDGETING PRACTICES FOR EFFECTIVE FINNANCIL MANAGEMENT IN PUBLIC AND PRIVATE SECONDARY SCHOOLS IN ANAMBRA STATE. (UNIZIK Journal of Educational Management and Policy, 2026)
The study compared comparative analysis of principals’ application of budgeting practices foreffective financial management in public and private secondary schools in Anambra state. Tworesearch questions guided the study and two null hypotheses were tested at 0.05 alpha level.Descriptive Survey research design was adopted for this study. The population of the studycomprised 1127 principals, 268 public and 859 private secondary schools in Anambra State.Through a multistage sampling procedure, procedure sample a total of 295 (70 public and 225private) principals were selected. A questionnaire titled " Comparative Analysis of Principals’Application of Budgeting Practices for Effective Financial Management Questionnaire(CAPABPEFMQ)" was the instrument used for data collection. The instruments were facevalidated by three experts who were lecturers in the department of educational management andpolicy and measurement and evaluation in the department of Educational Foundation in Facultyof Education all in Nnamdi Azikiwe University Awka. Reliability of the instrument was establishusing Cronbach alpha method which yielded the overall coefficient was 0.89. Mean and Standarddeviation was used to answer research questions, while t-test was use to test the hypotheses. Thefindings of the study revealed among others that principals in both public and private secondaryschools agreed that incremental budgeting practices are applied in managing school finances.Based on the findings, it was recommended among others that the principals in both public andprivate secondary schools in Anambra State should embark on regular and continuous trainingsuch as seminars, workshops, conference on budgeting and financial management for continuousimprovement on budget application.
Keywords: Principals, Budgeting Practices, Financial Management, Secondary School